The role of S-nitrosylation of PFKM in regulation of glycolysis in ovarian cancer cells - Gao, Wenwen (Cell Death Dis, 2021)
One of the malignant transformation hallmarks is metabolism reprogramming, which plays a critical role in the biosynthetic needs of unchecked proliferation, abrogating cell death programs, and immunologic escape. However, the mechanism of the metabolic switch is not fully understood. Here, we found that the S-nitrosoproteomic profile of endogenous nitrogen oxide in ovarian cancer cells targeted multiple components in metabolism processes. Phosphofructokinase (PFKM), one of the most important regulatory enzymes of glycolysis, was S-nitrosylated by nitric oxide synthase NOS1 at Cys351. S-nitrosylation at Cys351 stabilized the tetramer of PFKM, leading to resist negative feedback of downstream metabolic intermediates. The PFKM-C351S mutation decreased the proliferation rate of cultured cancer cells, and reduced tumor growth and metastasis in the mouse xenograft model. These findings indicated that S-nitrosylation at Cys351 of PFKM by NOS1 contributes to the metabolic reprogramming of ovarian cancer cells, highlighting a critical role of endogenous nitrogen oxide on metabolism regulations in tumor progression.